2003
DOI: 10.1038/sj.ejcn.1601527
|View full text |Cite
|
Sign up to set email alerts
|

Bone resorption in anorexia nervosa and rehabilitated patients

Abstract: Objective: To assess the impact of anorexia nervosa and that of nutritional rehabilitation on bone resorption. Design: Cross-sectional, observational study. Setting: Rome, Italy Subjects: Twenty-eight female patients affected by anorexia nervosa (AN, BMI 17.0 kg=m 2 ), 18 females rehabilitated from anorexia nervosa and weight-stable for at least 6 months (RE, BMI ! 18.5 kg=m 2 ) and 34 age-and sex-matched healthy controls (CO, BMI ! 18.5 kg=m 2 ). Among AN patients, 16 were affected by the 'restrictive' (ANr) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…In multiple studies, bone turnover was found to be altered in patients with AN [ 30 , 47 , 48 ]. Bone turnover refers to the balance between bone resorption and bone formation as measured by markers from the peripheral blood or urine.…”
Section: Methodsmentioning
confidence: 99%
“…In multiple studies, bone turnover was found to be altered in patients with AN [ 30 , 47 , 48 ]. Bone turnover refers to the balance between bone resorption and bone formation as measured by markers from the peripheral blood or urine.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, during adolescence there is a physiological increase in bone mass, 55–57 and the gap between normal subjects and anorexia nervosa patients tends to widen with amenorrhoea duration. Furthermore, there are some data indicating that bone resorption may be accelerated even in some of the recently rehabilitated patients 58–59 . This indicates that bone mineral density (BMD) should be monitored well beyond recovery of body weight.…”
Section: Pathogenesis Of Bone Loss In Anorexia Nervosamentioning
confidence: 99%
“…Furthermore, there are some data indicating that bone resorption may be accelerated even in some of the recently rehabilitated patients. [58][59] This indicates that bone mineral density (BMD) should be monitored well beyond recovery of body weight.…”
Section: Restrictive Eating Behaviors Have Important Consequences On mentioning
confidence: 99%
“…Studies of short to medium-term recovery (less than 5 years), have suggested that increased bone resorption may persist for up to six months [51], that reductions in bone density may not be reversed [34,45,52] and that premenopausal fracture rates may be 2-7 times in excess of that expected [34,53]. In a controlled study, Soyka et al [54] found that during recovery over 1 year, bone mineral accrual was poor in girls with AN, in contrast to rapid bone accrual in healthy adolescents.…”
Section: Bone Healthmentioning
confidence: 99%